2018
DOI: 10.1038/s41423-018-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms implemented by human acute myeloid leukemia cells to suppress host immune surveillance

Abstract: Acute myeloid leukaemia (AML) is a blood/bone marrow cancer originating from myeloid cell precusors capable of self-renewing. AML cells implement biochemical mechanisms which allow them not only to survive, but also to successfully escape immune surveillance. ln this work, we discuss crucial molecular mechanisms used by human AML cells in order to evade immune attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Acute myeloid leukemia (AML) is a blood/bone marrow cancer originating from myeloid precursors, which rapidly progresses into a systemic and often a fatal malignancy. Human AML cells operate a variety of biochemical mechanisms which allow them to escape host immune surveillance (1). These molecular pathways cause impairment of the anti-cancer activities of natural killer (NK) cells and cytotoxic T cells which could otherwise attack and kill AML cells (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute myeloid leukemia (AML) is a blood/bone marrow cancer originating from myeloid precursors, which rapidly progresses into a systemic and often a fatal malignancy. Human AML cells operate a variety of biochemical mechanisms which allow them to escape host immune surveillance (1). These molecular pathways cause impairment of the anti-cancer activities of natural killer (NK) cells and cytotoxic T cells which could otherwise attack and kill AML cells (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Human AML cells operate a variety of biochemical mechanisms which allow them to escape host immune surveillance (1). These molecular pathways cause impairment of the anti-cancer activities of natural killer (NK) cells and cytotoxic T cells which could otherwise attack and kill AML cells (1,2). It has recently been reported that one of these immune evasion pathways includes high expression/ secretion of the protein galectin-9, its receptor and its possible trafficker/carrier (as with all galectins, galectin-9 requires a carrier protein-trafficker to be secreted) -the T cell immunoglobulin and mucin domain containing protein 3 (Tim-3) (3-6).…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-9 is one of the crucial proteins used by various types of cancer cells to suppress cytotoxic immune responses and thus, escape immune surveillance [1]. Some cancer cells (acute myeloid leukaemia (AML) and colorectal cancer) are capable of secreting this protein, while other cancer cells translocate galectin-9 onto the surface [1] and use it to impair anti-cancer activities of cytotoxic lymphoid cells such as cytotoxic T lymphocytes and natural killer (NK) cells [1][2][3][4][5][6]. Galectin-9 lacks a secretion signal sequence and thus cannot be secreted on its own.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data have shown that tumor-infiltrating NK cells exhibit poor cytotoxic capacity, accompanied by downregulation of activating receptors and upregulation of inhibitory receptors, compared with NK cells in non-tumor tissues (4,30,31). The tumor microenvironment is a complex network comprising regulatory T cells (Tregs), tumor-associated macrophages (TAMs), regulatory γδT cells, myeloid-derived suppressor cells (MDSCs), soluble factors, the extracellular matrix, and suppressive molecules expressed on tumor cells (32)(33)(34)(35). NK cell proliferation and antitumor activity are suppressed by tumor cell secretion of various immunosuppressive factors, including prostaglandin E2, indoleamine 2,3-dioxygenase (IDO), interleukin 10 (IL-10), transforming growth factor-β (TGF-β), and vascular endothelial growth factor.…”
Section: Effect Of the Tumor Microenvironment On Nk Cells' Cytolyticmentioning
confidence: 99%